Marriage in the Western Church : the Christianization of marriage during the patristic and early medieval periods - Reynolds, Philip Lyndon, 1950- (Vigiliae Christianae, Supplements, 1994)
Marriage in the Western Church examines how marriage acquired a specifically Christian identity in the Western Church from the patristic through Carolingian periods. It shows how theologians came to regard marriage as an ecclesiastical institution and how they developed a Christian theology of marriage. The first part of the book deals with marriage and divorce in Roman and Germanic law. Other parts deal with marriage and divorce in ecclesiastical law, with the Latin Fathers' distinction between the divine and human laws of marriage, and with the customary stages by which persons became married. Several chapters are devoted to Augustine's views on marriage and sexuality. The author shows how the doctrine of indissolubility became the West's chief means of christianizing marriage, and how theologians found here their preferred arguments for affirming the holiness and the 'sacramentality' of marriage. The author argues that the Western regime of indissolubility was the product of a fourth century reform movement. This publication has also been published in paperback, please click here for details.